Validation of clinical T stage using depth of invasion in the patients with oral squamous cell carcinoma and its correlation with imaging - Mahesh Sultania; Priyansh Jain; Itisha Chaudhary; Hemanth Ghalige; Simran Sidhu; Sudipta Mohakud; G. Sudhakar; K. Raghuram; Dillip Muduly; Amit Adhya; Sandip Barik; Saroj Majumdar; et al. (Oral Oncology Reports)
Objective The preoperative (clinical and radiological) depth of invasion (DOI) in early tumours can guide the surgeons in deciding elective neck dissection, the extent of invasive surgery, the need for reconstruction, potential adjuvant treatment and the patient's prognosis. This study aimed to validate the 8th AJCC clinical T stage using DOI, assess interobserver bias, and correlate the clinical, radiological and pathological T stages. Materials and methods: This was a prospective clinical study carried out from December 2019 to June 2023 at an academic tertiary care centre. Patients with squamous cell carcinoma of oral cavity and lip without involvement of skin or bone undergoing upfront surgery were included. The clinical assessment of T stage using DOI was done by three examiners, blinded to each other. The radiological T stage was assessed by an MRI and pathological T stage on fixed formalin surgical specimen. Results: A total of 173 patients were assessed during the study period, out of which 44 met the inclusion criteria. There was a fair agreement regarding the combined clinical T stage between all three examines. A statistically significant correlation was found between the clinical and pathological T stage (p-value 0.010), the radiological and pathological T stage (p-value 0.001) and clinical and radiological T stage (p-value 0.004). Conclusion: The clinical and radiological T stage using DOI correlated well with the pathological T stage. The 8th AJCC clinical T stage of oral squamous cell carcinoma was accurate in our study population.